METODOLOGI PEMIKIRAN KEWARISAN MAULANA SYEKH ZAINUDDIN ABDUL MADJID: INTEGRASI BAYANI DAN MAQASIDI DALAM KONTEKS SOSIAL MASYARAKAT SASAK - Tuti Munawarah; Andi St Nur Azizah Akram (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the methodology of the inheritance of Maulana Sheikh Zainuddin Abdul Madjid in the context of the Sasak Lombok community. The focus of the research is directed at methodological character analysis that combines the bayani approach that relies on the text of the Qur'an, hadith, and ijma' with a maqasidi approach that considers social benefits. This research uses a qualitative method with a library research approach, through an analysis of the main works of Maulana Sheikh, especially Tuhfah al-Zainiyyah and other supporting literature. The results of the study show that normatively Maulana Shaykh affirmed the distribution of inheritance based on furudh al-muqaddarah as stated in Surah An-Nisa verses 11–12. However, in social practice, Maulana Sheikh offers a grant pattern as a transitional solution for people who have not fully accepted the faraidh system formally. This pattern reflects the integration between textual legitimacy (bayani) and consideration of benefits (maqasidi) applied contextually in Sasak society. The contribution of this research lies in the affirmation of the methodological character of Maulana Shaykh's inheritance thought as an integrative model between normative texts and local social realities, which enriches the study of Islamic family law based on local wisdom.